Defining the tipology of islamic architecture case study: bayt al qur’an building & istiqlal museum - Wahid, Julaihi; Alamsyah, Bhakti (2008)

(untitled)
The progress of industrial technology allows man to make a several changes and new inventions, including the creation of architectural feats. From the dawn of the civilization, the homo sapiens led a nomadic life and took shelter from the caves or the top of the trees until they settle down and make hut in special places on the earth surface i.e along the river banks, the lowlands and the hill tops. The need to be sheltered from the elements of nature is intensively developed and from here architecture started to advance in enhancing the complexity of building design. The appearance of the new form in the building design sometimes triggers the debate especially the idea of “concept, technique, function as well as the environmental considerations”. Actually, the new form in building design originated from various basic design principles which emerge from the concepts of the architect. Likewise, Achmad Noe’man one of the famous architects in Indonesia, attempts a new approach in the building design through conceptualizing the true faith of Islam and the motives of Islamic elements in the building designs. The Bayt Al Quran and Istiqlal Museum are a good example where the architect portrays the significant of Islamic elements and concepts in the buildings. In this paper the author attempt to examine and discuss the buildings that has been designed by the architect and analyze the cases in order to find out how the new ‘typology’ emerged with his conceptualizing of the Islamic faith in the building where as the prevalent architects develop conventional architecture to match the rapid development which favored the modernist approach.